Disinkroni Ventrikel Pada Pacu Jantung Permanen Dengan Elektroda di Apex dan Alur Keluar Ventrikel Kanan: Evaluasi Menggunakan Tissue Doppler Imaging - Wisnoe Pribadi; Manoefris Kasim; Iwan Dakota (The Indonesian Heart Association, 2007)
Background : Pacemaker lead implantation at right ventricular apex (RVA) or right ventricular outflow tract (RVOT) have different haemodynamic consecuences, due to ventricular dyssynchrony difference. Tissue Dop-pler Imaging (TDI) clearly shown ventricle dyssynchrony, this modality is better than convensional echo. This research was performed using TDI to describe ventricle dyssynchrony in RVA and RVOT pacing.Method and Result: Twenty four patients with VVI/VVIR pacemaker in-serted at the Catheterization Laboratory National Cardiac Centre Harapan Kita Hospital were evaluated using TDI modality for ventricle dyssynchrony. Subject characteristic consist of 13 men (54,8%) and 11 (45,8%) women, with average of age were 61,38 ± 12,41 years. Base rhythm were Sick Sinus Syndrome/SSS (37,5%) and Total Atrioventricular Block/TAVB (62,5%). The duration of implantation was 24,83 ± 16,88 months, with minimal duration of pacing 1 month and maximal duration 63 months. The average of ventricular ejection fraction was 0,45±0,15. Chi Square ana-lyze have shown that there were no difference dyssynchrony between RVA and RVOT pacing, p=0,408 for inter ventricular delay and p=0,423. for intra ventricular delay. QRS duration after pacing have shown signifi-cant difference between the two groups (p=0.01).Conclusion : There were no difference in ventricular dyssynchrony be-tween RVA and RVOT pacing, but QRS duration at the RVOT pacing is significantly shorter than RVA pacing.